Effective British and American Pronunciation Learning Strategies for Students - Agnes Corint Sembiring; Cindy Patricia Manurung; Hesti Fera Sinaga; Yesi Rela Saogo; Bloner Sinurat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
A key difficulty for individuals learning English as an Additional Language (EAL) remains pronunciation, particularly in recognizing the differences between American English (AmE) and British English (BrE) norms. This research explores strategies to assist learners in accurately articulating and understanding the distinctive phonetic traits of both forms of English. The research highlights the significance of diverse techniques such as organized shadowing, phonetic notation, sound differentiation exercises, and engaging pronunciation applications.Carried out over a period of two months involving 30 students with intermediate skills, the research indicated that using real native resources, participating in peer correction exercises, and maintaining regular pronunciation records greatly aided in enhancing the learners’ skills. Additionally, the learners showed an increased understanding of accent differences and built their confidence in switching between British English and American English based on the context of communication. This study adds value to the increasing demand for flexible pronunciation teaching that recognizes the worldwide variety of English and fosters learner independence.